Integrating the Colon Leakage Score (CLS) and Serum Albumin to Predict Anastomotic Leakage in Colorectal Cancer Surgery: A Diagnostic Accuracy Study in an Indonesian Cohort - Muhammad Rizqi Firyal; Muhammad Hafidh Komar; Theodorus (Sriwijaya Journal of Surgery, 2025)
Introduction: Anastomotic leakage (AL) is a devastating complication in colorectal surgery, associated with high rates of morbidity and mortality. Accurate preoperative risk stratification is essential for guiding clinical decision-making. This study aimed to evaluate the diagnostic accuracy of a synergistic model combining the clinical Colon Leakage Score (CLS) with the biochemical marker of preoperative serum albumin for predicting AL in an Indonesian patient cohort. Methods: A retrospective diagnostic accuracy study was conducted at a single tertiary care center. The study included 60 patients who underwent resection and primary anastomosis for colorectal cancer between January 2022 and June 2024. Patients who received a diverting stoma were excluded. A "high-risk" status was defined by a composite criterion: a CLS > 11 and a preoperative serum albumin level < 3.5 g/dL. The primary outcome was clinically significant AL. Following the identification of inconsistencies in the initial analysis, a complete data re-analysis was performed. Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values, and overall accuracy, with 95% confidence intervals (CI), were calculated. Results: The incidence of AL was 21.7% (13/60 patients). A striking 71.7% of the cohort presented with preoperative hypoalbuminemia. The analysis revealed that the combined model demonstrated poor sensitivity of 46.2% (95% CI: 19.2% - 74.9%) but excellent specificity of 97.9% (95% CI: 88.7% - 99.9%). The model yielded a high PPV of 85.7% (95% CI: 42.1% - 99.6%) and a robust NPV of 86.8% (95% CI: 75.0% - 94.6%). The overall accuracy was 86.7%. Conclusion: The combined CLS-albumin model functions as a highly specific "rule-in" test, not a general screening tool. While it fails to identify more than half of the patients who will leak, a positive result correctly identifies a small subset of patients at extremely high risk for anastomotic leakage. The findings also highlight a profound baseline burden of malnutrition in this population, which warrants further investigation and clinical attention.